Population variation in admission rates and duration of inpatient stay for bronchiolitis in England. Issue 1 (5th December 2012) - Cheung, C Ronny; Smith, Helen; Thurland, Kate; Duncan, Helen; Semple, Malcolm G
Abstract : Aim: To explore the variation in hospital admission rates and duration of inpatient stay across England. Methods: Hospital Episode Statistics were used to identify all children aged below 2 years who were discharged from hospital with a primary code of bronchiolitis in England, between 1 April 2007 and 31 March 2010; rates of admission and duration of stay were analysed by Primary Care Trust (PCT). Results: There were a total of 75 318 admissions for bronchiolitis in England in children under 2 years old during the study period. There was a 15-fold variation across PCTs in England in the admission rate for bronchiolitis (351–5140 admissions per 100 000; coefficient of variation (CV)=0.43) and a sixfold variation in the mean duration of stay in days for children with bronchiolitis (0.7–4.1 days in hospital; CV=0.27). Duration of stay was not correlated with socioeconomic deprivation, while admission rates showed variation even among PCTs of similar socioeconomic profile. Conclusions: We postulate that healthcare provider factors manifested by variation in clinical decision-making (including thresholds for admission and discharge, and variation in therapies) are responsible at least in part for variation in rate of admission and length of stay for children with bronchiolitis in England.